HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG COVID-19 DENGAN PENERAPAN PROTOKOL KESEHATAN DI ERA NEW NORMAL - Rahmah Rahmah; Jaenudin Jaenudin; Zahrah Maulidia Septimar (Nusantara Hasana Journal, 2021)
Based on the preliminary study, it was found that 8 out of 10 people already know about Corona Virus Disease (Covid-19) and already know how to implement good and correct protocols to prevent the transmission of Covid-19 and 2 other people don't know. For this reason, it is necessary to increase public knowledge about COVID-19 in the application of health protocols. Research Objectives: to determine the relationship between the level of public knowledge and the application of health protocols during the pandemic in Kp. Sepatan Rt.01 Rw.01. Knowledge. Research Methods : This research is a quantitative research with a descriptive analytical quantitative research design. The instrument used is a questionnaire and the analytical test used is the chi square test.. Research Results : Based on the results of the analysis of the chi square test, it produces a value of Sig = 0.000 on the variable level of knowledge. Then it can be concluded "Ha accepted" (Sig 0.000 <0.05). Conclusion: There is a relationship between the level of knowledge with the application of health protocols in Kp. Sepatan Rt.01 Rw.01.. Suggestion: Hopefully it can be useful for readers.